Indoor Deterministic Simulations and Statistical Modeling at Sub-THz Frequencies for Future Wireless Networks - Nektarios Moraitis; Konstantina S. Nikita (IEEE Open Journal of Antennas and Propagation)
Next generation wireless networks will necessitate new and wide spectrum swaths able to accommodate and support Tb/s applications and services. In this regard, frequencies above 100 GHz are anticipated to be allocated, which requires a thorough analysis of the propagation characteristics at those segments. This article presents a detailed analysis of the indoor channel at sub-THz frequencies, modeling its temporal and spatial characteristics for line-of-sight (LOS) and non-line-of-sight (NLOS) conditions, relying on extensive deterministic simulations. According to the results, frequency selective characteristics are revealed. The obtained root-mean-square delay spread is in the range of 4.4–10.3 ns for LOS, and 6.9–18.8 ns for NLOS scenarios, respectively. A high spatial degree of freedom is also observed based on the increased azimuth spreads with a mean value of 57.4° for LOS, and 88.1° for NLOS locations, which is associated with the environment geometry. All the large-scale features of the channel exhibit a linear variation with distance, whereas according to the Gini Index and K-factor analysis, a channel with limited sparsity is encountered, especially in NLOS scenarios. Furthermore, the spatial coherence of the channels’ attributes is also assessed and modeled using an exponential decaying sinusoid relationship. A faster channel decoherence is observed in NLOS locations. Finally, the temporal and spatial properties of the channel are modeled statistically, delivering its related features that include the ray and cluster decaying rates, the inter-arrival delays, the azimuth and elevation angle-of-arrivals, and the cluster and ray occurrence.